Can playing an "unfair game" promote ethical decision-making? The use of the "trading game" in secondary-school geography lessons. Issue 3 (3rd July 2021) - Hofmann, Jan
Abstract: The dual factual and ethical dimension of learning in geography calls for consideration of how pupils in schools handle this complexity and how teachers might promote the development of ethical decision-making skills in the geography classroom. Proceeding from, and taking a new theoretical approach to, intuitive ethics, this article demonstrates the particular utility of the "trading game" as a learning setting for promoting ethical decision-making in the geography classroom. The researcher analysed the group discussions that took place subsequently to the use of the game via the documentary method, and, in line with reconstructive qualitative research practices, developed a typology that illuminated the decision-making logics driving pupils' gameplay and their engagement with the dual complexity of factual and ethical learning in geography lessons. The findings point to implications for didactic and methodological practice with regard to the type-specific promotion and development of ethical decision-making in the geography classroom.